Response Rate and Impact on Lipid Profiles of Obeticholic Acid Treatment for Patients with Primary Biliary Cholangitis: A Meta-Analysis - Yuan Gao; Li Li; Bei Li; Yutao Zhan (Canadian Journal of Gastroenterology and Hepatology)
Background. Up to 40% of patients with primary biliary cholangitis (PBC) have an inadequate response to ursodeoxycholic acid (UDCA). Obeticholic acid (OCA) is considered the addition of treatment, but the response rate based on commonly referenced biochemical response criteria and lipids’ impact was unclear. Previous studies reported inconsistency results partially due to small sample size. Therefore, we performed a meta-analysis and aimed to explore OCA treatment’s response rate and effect on lipids’ profiles in PBC patients. Methods. We performed PubMed, Embase, and Cochrane controlled trials register (updated to JUN 2019) databases and manual bibliographical searches for randomized controlled trials reporting on OCA treatment in PBC patients. Two researchers independently extracted data and assessed the risk of bias of studies. We calculated risk ratio (RR) for the overall complete response rate, and the standardized mean difference (SMD) for the serum lipids changes after OCA treatment, all with 95% confidence intervals (CIs) using fixed-effects models. We registered this meta-analysis with PROSPERO (registration number: CRD42020148550). Results. Three trials, with 265 patients, were selected for the analysis. OCA was superior to placebo in PBC patients (RR, 1.48; 95% CI, 1.15–1.90). OCA’s pooled treatment response rate was 65% (95% CI, 56%–74%), corresponding to Paris I criteria. Besides, OCA significantly decreased total cholesterol (P=0.02) with no heterogeneity (P=0.87, I2 = 0%) and high-density lipoprotein levels (P<0.05) with no heterogeneity (P=0.82, I2 = 0%). Conclusions. This meta-analysis demonstrated that OCA was a promising additional treatment for PBC patients and might reduce serum cholesterol levels. The longer follow-up studies are needed to give more evidence.